The Severity of Neurological Dysfunction in Preschool Children, Secondary to Damage Generated During the Perinatal Period, is Associated With a Pro-Inflammatory Pattern of Serum Molecules - Madrid, Miriam; Brianza-Padilla, Malinalli; Echeverría, Juan C.; Rivera-González, Rolando; Bojalil, Rafael (Frontiers in Immunology, 2021)
Disorders in the child’s neurodevelopment provoked by perinatal risks may result in long-term altered neurological signs initiated at an early age, which imply persistent functional disarrangements. Recent data suggest that tissue dysfunction, and not only acute damage, can initiate or perpetuate an inflammatory response. The aim of this study was to find out if in preschool children any neurological dysfunction secondary to a damage generated during the perinatal period is associated with the magnitude of perinatal risks and with long-term modifications in the concentrations of inflammatory molecules. Participants, 1-4 years old, were in neurodevelopmental follow-up and rehabilitation therapy from the first three months of life and had no data of acute diseases. We classified children in 3 groups based on the importance of their perinatal risks: low, medium and high. The results show that 1) the magnitude of perinatal risks correlates with the severity of neurological disfunction, and 2) the greater changes in concentrations of molecules of the inflammatory process were associated with the most altered neurological signs. This suggests that persistent nervous system dysfunction keeps inflammatory responses active even in the absence of an acute process of infection or damage.